Biological and biochemical properties of the Brazilian Potamotrygon stingrays : Potamotrygon cf. scobina and Potamotrygon gr. orbignyi - Magalhaes, K. W.; Lima, C.; Piran-Soares, A. A.; Marques, E. E.; Hiruma-Lima, C. A.; Lopes-Ferreira, M. (Elsevier B.V., 2006)
Stingrays of the family Potamotrygonidae are widespread throughout river systems of South America that drain into the Atlantic Ocean. Some species are endemic to the most extreme freshwater environment of the Brazil and cause frequent accidents to humans. The envenomation causes immediate, local, and intense pain, soft tissue edema, and a variable extent of bleeding. The present study was carried out in order to describe the principal biological and some biochemical properties of the Brazilian Potamotrygon fish venoms (Potamotrygon cf. scobina and P. gr. orbignyi). Both stingray venoms induced significant edematogenic and nociceptive responses in mice. Edematogenic and nociceptive responses were reduced when the venom was incubated at 37 or 56 degrees C. The results showed striking augments of leukocytes rolling and adherent cells to the endothelium of cremaster mice induced by both venoms. The data also presented that injection of both venoms induced necrosis, low level of proteolytic activity, without inducing haemorrhage. But when the venoms of both stingray species were injected together with their mucus secretion, the necrotizing activity was more vigorous. The present study provided in vivo evidence of toxic effects for P. cf. scobina and P. gr. orbignyi venoms. (c) 2006 Elsevier Ltd. All fights reserved.
Keywords: Potamotrygon venoms; stingrays; biological and biochemical activities